THE RIGHT OF SELF-DEFENSE AND THE ORGANIC UNITY OF HUMAN RIGHTS - Little, David (Journal of law and religion, 2021)
The article challenges the fashionable but finally unsupportable opinion in political and academic circles that there exists no compelling, unitary, universally resonant moral and legal justification of human rights. The argument is intimated by two overlooked passages in the preamble to the Universal Declaration of Human Rights that presuppose the right of self-defense against arbitrary force, understood as both a moral and legal concept, and as relevant both to personal and collective life. It shows how the logic of defensive force underlies the three formative human rights instruments: the UDHR, and the two covenants on political, legal, economic, social, and cultural rights. The underlying claim is that good reasons of a particular kind are required to justify any use of force, a claim that makes perfect sense against the backdrop of the atrocities committed by the German fascists and their allies in the mid-twentieth century. The article also refers to compelling, if preliminary, evidence of the widespread cross-cultural acceptance of the moral and legal right of self-defense, suggesting a basis for the worldwide comprehensibility and appeal of human-rights language.